Pengaruh Konsentrasi Zat Pengatur Tumbuh Sitokinin Dalam Pertunasan Jahe Emprit (Zingiber officinale var. Amarun) - Kirani, Devi; Herawati, Maria Marina (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the effect of cytokinin growth regulator concentration on the sprouting of ginger emprit, as well as to determine the most effective concentration in stimulating the growth of ginger emprit shoots optimally. This study was conducted during five months of observation from February 2024 to June 2024. Sampling was done with a group randomized design. The growth regulator used was cytokinin BAP (6-benzyln amino purine) with concentrations of 0 mg L-1, 200 mg L-1, 400 mg L-1, 600 mg L-1 and 800 mg L-1. The results showed that (1) there is a significant relationship between the growth of emprit ginger shoots and the concentration of cytokinin growth regulators; (2) the provision of cytokinin growth regulator BAP the higher the concentration given affects the growth of the number of shoots, shoot height, shoot growth, number of leaves and shoot weight of emprit ginger; (3) the treatment of cytokinin growth regulator immersion concentration of 800 mg L-1 gives a real effect on the growth of the number of shoots, the growth of the number of leaves and the height of ginger plants, but does not support the appearance of shoot growth and shoot weight.